2016
DOI: 10.1063/1.4961918
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-spark switch (PSS) characteristics under different operation conditions

Abstract: The present paper concentrates on the characteristics of the pseudospark switch (PSS) designed in a previous work. The special characteristics of PSS make it a replacement for other high voltage switches such as thyratrons and ordinary high-pressure spark gaps. PSS is characterized by short rise time and small jitter time. The pseudo park chamber consists of two hollow cylindrical electrodes made of a stainless steel material (type 306L) separated by an insulator. The insulator used in our design is a glazed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It needs to have the characteristics of low inductance and low resistance, which are far less than that of inductive coil load. TDI-series pseudospark switches [18,[22][23][24][25][26], also known as cold cathode thyratrons, work on the left-hand branch of the Paschen curve and are used as main switch and crowbar switch, as shown in figure 6. The TDI-series pseudospark switches have a ceramic/metal shell, filled with hydrogen (deuterium) as buffer gas at working pressure of 20-60 Pa.…”
Section: Pseudospark Switchesmentioning
confidence: 99%
“…It needs to have the characteristics of low inductance and low resistance, which are far less than that of inductive coil load. TDI-series pseudospark switches [18,[22][23][24][25][26], also known as cold cathode thyratrons, work on the left-hand branch of the Paschen curve and are used as main switch and crowbar switch, as shown in figure 6. The TDI-series pseudospark switches have a ceramic/metal shell, filled with hydrogen (deuterium) as buffer gas at working pressure of 20-60 Pa.…”
Section: Pseudospark Switchesmentioning
confidence: 99%
“…The discharge is sustained between the ring anode A 1 and the cathode C 1 due to the power supply V 1 . Typically, this is a steady state hollow-cathode glow discharge with a current of (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) the current flows to the electrode C 1 . This current will be denoted as i 1 .…”
Section: Principle Of Thyratron Operation As Applied To the Propomentioning
confidence: 99%
“…Then the terms cold-cathode thyratron or grounded-grid thyratron are also used in the current literature. [4][5][6][7] In early [1][2][3][4][5] and present-day [6][7][8][9][10][11][12][13][14][15][16] publications, there are described a variety of switch prototypes for different applications on the basis of the demountable experimental chambers with external gas filling. As a result of the investigations, the sealed-off switches had been developed 5 in which the operating gas pressure is maintained due to a heated hydrogen reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…The complex physical mechanism of hollow-cathode discharges and the interaction of the electron beam with the space charge plasma in a low-vacuum environment result in the formation of a unique spatial and temporal distribution of the electron beam current and energy [9][10][11][12][13]. It has been shown that hollow-cathode pulsed electron beam is characteristic with high current densities (10 2 -10 3 A/cm 2 ), high energy (10-40 keV), and short pulse durations (10 −7 -10 −6 s) in the earlier experimental researches [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%